Serum glial fibrillary acidic protein and neurofilament light chain in patients with early treated phenylketonuria - Lotz-Havla, Amelie S.; Katzdobler, Sabrina; Nuscher, Brigitte; Weiß, Katharina; Levin, Johannes; Havla, Joachim; Maier, Esther M. (Frontiers in Neurology, 2022)
To pave the way for healthy aging in early treated phenylketonuria (ETPKU) patients, a better understanding of the neurological course in this population is needed, requiring easy accessible biomarkers to monitor neurological disease progression in large cohorts. The objective of this pilot study was to investigate the potential of glial fibrillary acidic protein (GFAP) and neurofilament light chain (NfL) as blood biomarkers to indicate changes of the central nervous system in ETPKU. In this single-center cross-sectional study, GFAP and NfL concentrations in serum were quantified using the Simoa® multiplex technology in 56 ETPKU patients aged 6–36 years and 16 age matched healthy controls. Correlation analysis and hierarchical linear regression analysis were performed to investigate an association with disease-related biochemical parameters and retinal layers assessed by optical coherence tomography. ETPKU patients did not show significantly higher GFAP concentrations (mean 73 pg/ml) compared to healthy controls (mean 60 pg/ml, p = 0.140). However, individual pediatric and adult ETPKU patients had GFAP concentrations above the healthy control range. In addition, there was a significant association of GFAP concentrations with current plasma tyrosine concentrations (r = −0.482, p = 0.036), a biochemical marker in phenylketonuria, and the retinal inner nuclear layer volume (r = 0.451, p = 0.04). There was no evidence of NfL alterations in our ETPKU cohort. These pilot results encourage multicenter longitudinal studies to further investigate serum GFAP as a complementary tool to better understand and monitor neurological disease progression in ETPKU. Follow-up investigations on aging ETPKU patients are required to elucidate the potential of serum NfL as biomarker.